Histone Deacetylases and Their Inhibition in Candida Species - Garnaud, Cécile; Champleboux, Morgane; Maubon, Danièle; Cornet, Muriel; Govin, Jérôme (Frontiers in Microbiology, 2016)
Fungi are generally benign members of the human mucosal flora or live as saprophytes in the environment. However, they can become pathogenic, leading to invasive and life threatening infections in vulnerable patients. These invasive fungal infections are regarded as a major public health problem on a similar scale to tuberculosis or malaria. Current treatment for these infections is based on only four available drug classes. This limited therapeutic arsenal and the emergence of drug-resistant strains are a matter of concern due to the growing number of patients to be treated, and new therapeutic strategies are urgently needed. Adaptation of fungi to drug pressure involves transcriptional regulation, in which chromatin dynamics and histone modifications play a major role. Histone deacetylases (HDACs) remove acetyl groups from histones and actively participate in controlling stress responses. HDAC inhibition has been shown to limit fungal development, virulence, biofilm formation and dissemination in the infected host, while also improving the efficacy of existing antifungal drugs towards Candida spp. In this article, we review the functional roles of HDACs and the biological effects of HDAC inhibitors on Candida spp., highlighting the correlations between their pathogenic effects in vitro and in vivo. We focus on how HDAC inhibitors could be used to treat invasive candidiasis while also reviewing recent developments in their clinical evaluation.